Using historical genome‐wide DNA to unravel the confused taxonomy in a songbird lineage that is extinct in the wild - Baveja, Pratibha (Evol Appl, 2020)
Urgent conservation action for terminally endangered species is sometimes hampered by taxonomic uncertainty, especially in illegally traded animals that are often cross‐bred in captivity. To overcome these problems, we used a genomic approach to analyze historical DNA from museum samples across the Asian Pied Starling (Gracupica contra) complex in tropical Asia, a popular victim of the ongoing songbird crisis whose distinct Javan population (“Javan Pied Starling”) is extinct in the wild and subject to admixture in captivity. Comparing genomic profiles across the entire distribution, we detected three deeply diverged lineages at the species level characterized by a lack of genomic intermediacy near areas of contact. Our study demonstrates that the use of historical DNA can be instrumental in delimiting species in situations of taxonomic uncertainty, especially when modern admixture may obfuscate species boundaries. Results of our research will enable conservationists to commence a dedicated ex situ breeding program for the Javan Pied Starling, and serve as a blueprint for similar conservation problems involving terminally endangered species subject to allelic infiltration from close congeners.